2011
DOI: 10.1007/s10646-011-0776-0
|View full text |Cite
|
Sign up to set email alerts
|

Histologic, immunologic and endocrine biomarkers indicate contaminant effects in fishes of the Ashtabula River

Abstract: The use of fish as sentinels of aquatic ecosystem health is a biologically relevant approach to environmental monitoring and assessment. We examined the health of the Ashtabula River using histologic, immunologic, and endocrine biomarkers in brown bullhead (BB; Ameiurus nebulosus) and largemouth bass (Micropterus salmoides) and compared fish collected from a reference site (Conneaut Creek). Seasonal analysis was necessary to distinguish differences in fish between the two rivers. Overall BB from the Ashtabula … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 97 publications
1
7
0
Order By: Relevance
“…While the effect of food deprivation was generally greater than that for PCB exposure, PCB exposure did decrease bactericidal and oxidative burst activity. This result is consistent with those of previous studies in ictalurids [19,38,54], and suggests that PCB exposure may increase disease susceptibility, which could influence population demography. Notably, bactericidal activity returned to normal seven weeks after the start of a PCB-free diet, suggesting that the effect of PCBs on some immunological responses may be temporary.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…While the effect of food deprivation was generally greater than that for PCB exposure, PCB exposure did decrease bactericidal and oxidative burst activity. This result is consistent with those of previous studies in ictalurids [19,38,54], and suggests that PCB exposure may increase disease susceptibility, which could influence population demography. Notably, bactericidal activity returned to normal seven weeks after the start of a PCB-free diet, suggesting that the effect of PCBs on some immunological responses may be temporary.…”
Section: Discussionsupporting
confidence: 93%
“…The goal of the PCB exposure phase was to feed fish in the PF and PNF treatments PCB-spiked food until they reached a body burden of 5 mg/kg while feeding fish in the CF and CNF treatments unspiked food. A target concentration of 5 mg/kg was chosen because it is representative of the total body burden found in tissues of wild fish in PCB-contaminated environments [38]. As described below, we intended the PCB exposure phase to last for eight weeks; however, it took 11 weeks for fish in the PF and PNF treatments to reach the target body burden.…”
Section: Pcb Exposure Phasementioning
confidence: 99%
“…The AOC sites included the lower Ashtabula River located near Ashtabula, Ohio; the Trenton channel of the Detroit River sampled south of Detroit, Michigan; the lower Genesee River sampled near Rochester, New York; the lower Milwaukee River sampled near Milwaukee, Wisconsin and St. Louis Bay sampled near Duluth, Minnesota. Conneaut Creek, near Conneaut, Ohio, has been previously used as a reference site for comparison with the nearby Ashtabula River AOC [Iwanowicz et al, ]. In fall, fish were collected at the Ashtabula and Conneaut sites for a seasonal comparison.…”
Section: Methodsmentioning
confidence: 99%
“…injection of Aroclor 1238 (a PCB mixture) in brown bullhead, Ameiurus nebulosus , decreased bactericidal activity and circulating antibodies to Edwardsiella ictaluri [ 33 ]. In a field study, Iwanowicz and colleagues showed that brown bullheads in a PCB contaminated river had more macrophage aggregates and a reduced bactericidal and cytotoxic cell activity compared to the same species at a relative clean site [ 34 ]. It is interesting to mention that marked seasonal effects were observed in this field study.…”
Section: Immunomodulationmentioning
confidence: 99%